Experimental and Finite Element Analysis on the Structural Performance of Lightweight Hollow Slab Prefabricated Staircases - Jingmin Liu; Yiming Bao; Kang Qin (Buildings)
Prefabricated staircases are crucial components in modern architectural structures, but traditional concrete staircases are too heavy for efficient prefabrication, transportation, and construction. Therefore, this paper proposes a novel lightweight hollow slab prefabricated staircase (referred to as the KXB staircase). The staircase achieves hollow designs for steps and the baseplate by incorporating hollow tubes in the steps and adding polyethylene foam boards in the baseplate. Additionally, a standard prefabricated slab staircase (referred to as the CG staircase) was subjected to static loading tests to analyze failure characteristics, load-deflection curves, and strain distribution. A finite element model was created using ABAQUS (2020) and validated for accuracy through a comparison with experimental results. The results indicate that the novel lightweight hollow-slab prefabricated staircase surpasses conventional slab staircases in load capacity, deflection, and crack control. Furthermore, it achieves a 16% reduction in weight, a 28.6% improvement in load capacity, and a maximum error of 9.9% between the model and experimental results. The novel lightweight prefabricated staircase satisfies engineering requirements, minimizes transportation and hoisting costs, and demonstrates strong application potential.